2011
DOI: 10.1021/ja203340u
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Synthesis of Uniform and Extremely Small-Sized Iron Oxide Nanoparticles for High-Resolution T1 Magnetic Resonance Imaging Contrast Agents

Abstract: Uniform and extremely small-sized iron oxide nanoparticles (ESIONs) of < 4 nm were synthesized via the thermal decomposition of iron-oleate complex in the presence of oleyl alcohol. Oleyl alcohol lowered the reaction temperature by reducing iron-oleate complex, resulting in the production of small-sized nanoparticles. XRD pattern of 3 nm-sized nanoparticles revealed maghemite crystal structure. These nanoparticles exhibited very low magnetization derived from the spin-canting effect. The hydrophobic nanopartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
895
2
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 874 publications
(926 citation statements)
references
References 90 publications
26
895
2
3
Order By: Relevance
“…However, there are several challenges for using T 2 contrast agents (for example, Feridex and Resovist) in the clinic. As they are intrinsically negative contrast agents, falsepositive diagnosis may be found in the hypointense areas, such as blood pooling, calcification and metal deposition [9][10][11] . In particular, these commercially available T 2 contrast agents were synthesized in aqueous media and, consequently, exhibit poor crystallinity and relatively low relaxivity 12 .…”
mentioning
confidence: 99%
“…However, there are several challenges for using T 2 contrast agents (for example, Feridex and Resovist) in the clinic. As they are intrinsically negative contrast agents, falsepositive diagnosis may be found in the hypointense areas, such as blood pooling, calcification and metal deposition [9][10][11] . In particular, these commercially available T 2 contrast agents were synthesized in aqueous media and, consequently, exhibit poor crystallinity and relatively low relaxivity 12 .…”
mentioning
confidence: 99%
“…This drawback has focused research on finding methods for developing IONPs that serve as positive contrast agents for T1-weighted MRI. Studies have demonstrated that the downsizing of IONP core or coating thickness causes a shift on the NP magnetic behavior from superparamagnetic towards paramagnetic, thus creating T1-weighted MRI contrast agents [72,[87][88][89].…”
Section: Iron Oxide Nanoparticles (Ionps)mentioning
confidence: 99%
“…This class of probe primarily consists of Gd(III)-based complexes; incorporation of these smart probes into the NPs will further enhance their efficiency in molecular imaging applications. Very recently, the use of an improved hydrolysis method of inorganic salts assisted by incubation in a water bath led to water-soluble extremely small-sized metal-iron oxide NPs (IONPs), iron-oxide based NPs: MFe 2 O 4 (ESIONs) (M = Fe, Zn, Ni) NPs with average sizes of 4-5 nm [76,77] . The r 1 relaxivities and the r 2 /r 1 ratios of these NPs were more than 5 and < 3, respectively, which indicated that they were good candidates as T 1 -weighted MRI CAs.…”
Section: I)mentioning
confidence: 99%
“…To solve this problem, specific methods based on either pulse sequences [101,102] , design [103] , or size control [76] of NPs have been developed by researchers to generate a bright contrast from the IONPs.…”
Section: T 2 Np-based Casmentioning
confidence: 99%